An Apela RNA-Containing Negative Feedback Loop Regulates p53-Mediated Apoptosis in Embryonic Stem Cells - Li, Mangmang (Cell Stem Cell, 2015)
Maintaining genomic integrity is of paramount importance to embryonic stem cells (ESCs), as mutations are readily propagated to daughter cells. ESCs display hypersensitivity to DNA damage-induced apoptosis (DIA) to prevent such propagation, although the molecular mechanisms underlying this apoptotic response are unclear. Here, we report the regulatory RNA Apela positively regulates p53-mediated DIA. Apela is highly expressed in mouse ESCs and is repressed by p53 activation, and Apela depletion compromises p53-dependent DIA. Although Apela contains a coding region, this coding ability is dispensable for Apela’s role in p53-mediated DIA. Instead, Apela functions as a regulatory RNA and interacts with hnRNPL, which prevents the mitochondrial localization and activation of p53. Together, these results describe a tri-element negative feedback loop composed of p53, Apela, and hnRNPL that regulates p53-mediated DIA, and further demonstrate that regulatory RNAs add a layer of complexity to the apoptotic response of ESCs following DNA damage.